Corporate governance failures : the role of institutional investors in the global financial crisis - Hawley, James P. (University of Pennsylvania Press, 2011)
Legal and financial practitioners and researchers investigate the role of institutional investors in the corporate governance failures that contributed to the recent global financial crisis. The authors also offer proposals to mitigate future pitfalls. This volume covers alternative financial investments, systemic risk, and responsible investment.- Resumé vydavatel
Revised proceedings of a two-day conference entitled Institutional Investors, Risk/Return, and Corporate Governance Failures : Practical Lessons from the Global Financial Crisis.
Keywords: řízení a správa společností; investice; finanční rizika; obchodní společnosti; finanční krize; corporate governance; investments; financial risks; corporations -- 2008-2009; financial crises -- 2008-2009; elektronické knihy; sborníky konferencí; electronic books; proceedings of conferences